Retrospective study on the occurrence of the feline lungworms Aelurostrongylus abstrusus and Troglostrongylus spp. in endemic areas of Italy. Issue 2 (February 2015) - Di Cesare, Angela; Di Francesco, Gabriella; Frangipane di Regalbono, Antonio; Eleni, Claudia; De Liberato, Claudio; Marruchella, Giuseppe; Iorio, Raffaella; Malatesta, Daniela; Romanucci, Maria Rita; Bongiovanni, Laura; Cassini, Rudi; Traversa, Donato
Highlights PCR was used to detect Aelurostrongylus abstrusus and Troglostrongylus brevior in the lungs of domestic cats. A. abstrusus was the predominant lungworm in cats, while T. brevior was present in a small number of cases.